Misconceptions of education students in translating expressions for verbal problems in multiplication and division of decimal numbers - Garcia, Zenaida L. (Animo Repository, 1994)
This experimental research determines some misconceptions in writing expressions for verbal problems in the multiplication and division of decimal numbers. The study further investigates whether significant differences exist between the fields of specialization and the year levels of Education students.One hundred twenty Education students of the Pangasinan State University - Bayambang Campus served as the subjects of the study. There were 15 Math minors and 15 Math majors from each year level.With the use of a word problem test, it was found out the subjects' errors were basically caused by their misconceptions in translating verbal problems in the multiplication and division of decimal numbers. Such misconceptions were in turn caused by inadequate and limited conceptions of the operations.In an attempt to improve the students' performance, interviews were conducted to clarify and modify misconceptions. This was indicated by significant differences in mean scores before and after the said interviews. Using the pretest and the OLSAT raw scores as covariates, the analysis of covariance (ANCOVA) revealed that the classification of students into minor and major groups resulted in a significant difference in the students' performance. This was in terms of translating verbal problems. The interaction between the field of specialization and the students' year level was not significant. The Math major students scored significantly higher than their Math minor counterparts at all year levels. The subjects continued to face difficulties when they wrote appropriate expressions for verbal problems in multiplication and division with numerical data. This led to a conflict between the correct operation and the constraints of the corresponding model. There was no progress in the students' performance in the word problems with respect to age.There is a need to provide students with efficient and effective mental strategies that will enable them to control the impact of these models. Because today's Education students are tomorrow's teachers, the teaching-learning style may perpetuate misconceptions and misunderstandings if they are not corrected.